2002
DOI: 10.1002/ajim.10144
|View full text |Cite
|
Sign up to set email alerts
|

Occupational injuries among Boston bicycle messengers

Abstract: Urban bicycle messengers are a poorly documented, largely unstudied workforce who suffer a very high rate of occupational injury.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
0
2

Year Published

2006
2006
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 15 publications
(13 reference statements)
1
21
0
2
Order By: Relevance
“…This was consistent with the study by Dennerlein and Meeker, 15 who found that the most common type of injury in their Boston commercial bicyclist cohort was bruising or contusions, and the most common cause for lost days of work was fractures. Our study found that commercial bicyclists sustained milder injuries overall.…”
Section: Discussionsupporting
confidence: 87%
“…This was consistent with the study by Dennerlein and Meeker, 15 who found that the most common type of injury in their Boston commercial bicyclist cohort was bruising or contusions, and the most common cause for lost days of work was fractures. Our study found that commercial bicyclists sustained milder injuries overall.…”
Section: Discussionsupporting
confidence: 87%
“…Additionally, the bicycle's ambiguous legal position with regard to traffic laws is equally useful to the messenger. Dennerlein and Meeker (2003), in their small study of Boston bike messengers, found that couriers have an injury rate three times higher than meat-packers-an occupation long considered to be America's most dangerous. The national average for injuries in the workplace is 3.0 lost days of work annually per 100 workers; meat-packers lose 15.6 days.…”
Section: A Brief History Of the Bicycle Messengermentioning
confidence: 95%
“…The latter is expressed in a 6 tot 7-fold increase in hospital costs [3]. Since it is estimated that 60-90% of bicycle accidents are not reported this number significantly underestimates the real number of yearly accidents [4].…”
Section: Introductionmentioning
confidence: 98%